Persepsi Generasi Milenial Terhadap Kualitas Produk, Harga dan Promosi Selama Berbelanja Online di Situs Marketplace Shopee - Nurdiana (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
This study aims to analyze the millennial generation's perceptions of product quality, price and promotion in shopping on the shopee marketplace site. This research is a type of qualitative approach research. Where a qualitative approach is an approach that in processing data presents, and summarizes data, does not use statistical and mathematical calculations. As for the type of study, it uses a descriptive type of study to find out how the millennial generation influences the shopee marketplace. The population of this study were students of Makassar State University who were Shopee customers. Where descriptive study is a process in solving the problem being studied by describing or describing an object. This research requires 5 respondents. Based on the results of descriptive studies or articles showing that the shopee marketplace site has a positive effect on product quality and promotion of buyer decisions on the shopee marketplace and Price has a positive and significant effect on Purchasing Decisions on the Shopee marketplace.